Effect of low-compression balls on wheelchair tennis match-play - Sindall, P; Lenton, J P; Malone, L; Douglas, S; Cooper, R A; Hiremath, S; Tolfrey, K; Goosey-Tolfrey, V (International journal of sports medicine, 2014)
The purpose of this study was to compare court-movement variables and physiological responses to wheelchair tennis match-play when using low vs. standard compression tennis balls. Eleven wheelchair basketball players were monitored during repeated bouts of tennis (20 min) using both ball types. Graded and peak exercise tests were completed. For match-play, a data logger was used to record distance and speed. Individual linear heart rate oxygen consumption relationships were used to estimate match-play oxygen uptake. Significant main effects for ball type revealed that total distance (P<0.05), forward distance (P<0.05), and average speed (P<0.05) were higher for play using a low-compression ball. A lower percentage of total time was spent stationary (P<0.001), with significantly more time spent at speeds of 1-1.49 (P<0.05), 1.5-1.99 (P<0.05) and 2.0-2.49 (P<0.05) m ∙ sec(-1) when using the low-compression ball. Main effects for physiological variables were not significant. Greater total and forward distance, and higher average speeds are achieved using a low-compression ball. The absence of any difference in measured HR and estimated physiological responses would indicate that players move further and faster at no additional mean physiological cost. This type of ball will be useful for novice players in the early phases of skill development.